Radiation exposure to the personnel in the operating room and in the pathology due to SLN detection with Tc-99m-nanocolloid in breast cancer patients - Brenner, W.; Ostertag, H.; Peppert, E.; Czech, N.; Kampen, W. U.; Muhle, C.; Lüttges, Jutta; Henze, E. (Nuklearmedizin - NuclearMedicine, 2000)
Aim of this study was to assess the radiation exposure for the personnel in the operating room and in the pathology laboratories caused by radioguided SLN localization in breast cancer. Methods: In 15 patients dose rates were measured at various distances from the breast and tumor specimens during operation and pathological work-up at 3-5 h after peritumoral injection of 30 MBq Tc-99m-nanocolloid. Results: The dose rates were 84.1 ± 46.4 μGy/h at 2.5 cm, 3.57 ± 2.14 μGy/h at 30 cm, 0.87 ± 0.51 μGy/h at 100 cm, and 0.40 ± 0.20 μGy/h at 150 cm in the operating room and 44.4 ± 27.8 μGy/h at 2.5 cm, and 1.66 ± 1.34 μGy/h at 30 cm in the pathology laboratories. From these data the radiation exposure was calculated for 250 operations per year assuming a mean exposure time of 30 min for the surgical team members and of 10 min for the pathology staff. Under these conditions the finger dose is 10.5 mGy for the surgeon, and 5.55 mGy for the pathologist. The wholebody doses are 0.45 mSv, 0.11 mSv, 0.05 mSv, and 0.21 mSv for the surgeon, the operating room nurse, the anesthetist, and the pathologist, respectively. Conclusion: Since the radiation risk to staff members is low, a classification of the personnel in the operating room and in the pathology laboratories as occupational radiation exposed workers is not necessary.
Keywords: Radiation exposure; sentinel lymph node; Tc-99m-nanocolloid; breast cancer